Fine mapping and identification of the bright green leaf gene BoBGL in Chinese kale (Brassica oleracea var. alboglabra) - Zhang, Qi; Wang, Chenchen; Song, Jialu; Gao, Liwei; Shen, Wenjie; Liu, Yi; Chen, Daozong; Tan, Chen (Frontiers in Plant Science, 2024)
IntroductionChinese kale (Brassica oleracea var. alboglabra), is an annual herb belonging to the Brassica genus of Cruciferae, and is one of the famous specialty vegetables of southern China. Some varieties show bright green leaf (BGL) traits and have better commerciality. However, the genes responsible for this trait remain unidentified.MethodsIn this study, gene mapping was measured by BSR-Seq and molecular marker analysis. Gene expression analysis was performed qRT-PCR. Cloning and sequence analysis of candidate genes were also performed.ResultsGenetic analysis revealed that the bright green leaf trait is a dominant trait governed by a single pair of genes. BSR-seq and molecular marker validation mapped the candidate interval to about 1.5 Mb on chromosome C8. After expanding the BC1 population and analyzing recombinant individuals, the interval was refined to approximately 102 kb on chromosome C8 (50,787,908- 50,890,279 bp). There are 24 genes in this region, and after annotation and expression analysis, BolC8t52930H (BoCER1.C8), associated with wax synthesis, emerged as a key candidate for BoBGL. We cloned this gene from both parents, revealing significant differences in their promoter regions. A co-segregation primer was subsequently developed and validated in a segregated population, with results consistent with expectations.DiscussionThe gene BoCER1.C8 is a potential candidate for controlling the bright green leaf trait in Chinese kale, and its function needs to be validated next. Mapping and cloning this gene is crucial to understanding wax synthesis regulation and developing new bright green leafy varieties of Chinese kale.